2014
DOI: 10.1007/s40688-013-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of School Psychologists Regarding Barriers to Response to Intervention (RTI) Implementation

Abstract: As Response to Intervention (RTI) models continue to be implemented, an important research question is how school psychologists are experiencing the transition to RTI practice. In order to better understand the experiences of school psychologists, interviews with seven practicing school psychologists regarding their perceptions of barriers and challenges to successful implementation of RTI were conducted. Participants identified a number of potential barriers and challenges, including the need for leadership, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
6
0
5
Order By: Relevance
“…Obtaining MTSS knowledge and skills is challenging and has been widely explored in the MTSS literature (Bambara, Goh, Kern, & Caskie, 2012;Dulaney, Hallam, & Wall, 2013;Harlacher & Siler, 2011;Lohrmann, Martin, & Patil, 2013;Marrs & Little, 2014). However, aligning comprehensive school counseling programs and MTSS shows promise in expanding the reach of school counselors and improving student outcomes (Chitiyo & Wheeler, 2009;Cressey et al, 2014;Eagle, Dowd-Eagle, Snyder, & Holtzman, 2015).…”
Section: Multi-tiered Systems Of Support and Comprehensive School Coumentioning
confidence: 99%
“…Obtaining MTSS knowledge and skills is challenging and has been widely explored in the MTSS literature (Bambara, Goh, Kern, & Caskie, 2012;Dulaney, Hallam, & Wall, 2013;Harlacher & Siler, 2011;Lohrmann, Martin, & Patil, 2013;Marrs & Little, 2014). However, aligning comprehensive school counseling programs and MTSS shows promise in expanding the reach of school counselors and improving student outcomes (Chitiyo & Wheeler, 2009;Cressey et al, 2014;Eagle, Dowd-Eagle, Snyder, & Holtzman, 2015).…”
Section: Multi-tiered Systems Of Support and Comprehensive School Coumentioning
confidence: 99%
“…It may be that at least some of those school psychologists who feared for their positions had little to no training in advocacy and their intransigence was borne of uncertainty about how to proceed. A recent study by Marrs and Little (2014) found that school psychologists' resistance was a significant barrier in implementing changes associated with Response to Intervention (a multitiered model of service delivery that assists students experiencing academic and social problems), a finding that led the study authors to urge further professional development to help address the resistance. A clear finding from the advocates in the present study was their agreement that school psychologists need to be explicitly trained in advocacy, with almost half suggesting such preparation start early.…”
Section: Challenges and Barriers To Advocacymentioning
confidence: 96%
“…Given the SSPCs' potential involvement in their states' systemic reform, the three core ideas identified in Theme 3, policy change, RtI/MTSS, and program evaluation, point out the field's ongoing efforts to improve the structure of school systems to better meet our students' diverse learning needs. The implementation of RtI/MTSS, for example, requires effective collaboration within a school system (e.g., general education, special education, administrators, supportive staff) and incorporation of EBPs in the design, implementation, and evaluation of policies and practices (Little, Marrs, & Bogue, 2017;Marrs & Little, 2014). Essential to RtI/MTSS is the use of evidence-based instruction and interventions within a continuum of tiered supports.…”
Section: Sspcs' Involvement In System Improvementmentioning
confidence: 99%
“…Our interview findings also suggest that school psychologists' involvement in the RtI/MTSS movement has promoted an emerging work of refining their job responsibilities as well as job evaluation procedures. However, the potential impact on current school psychology practitioners' professional identity and efficacy of such an initiative mentioned in the NASP domain Legal, Ethical, and Professional Practice remains understudied (Marrs & Little, 2014). For instance, while moving toward applying instruction-based models to identify and serve students with SLD, the traditional role and identity of the school psychologist as a psychometrician or tester may be challenged.…”
Section: Sspcs' Involvement In System Improvementmentioning
confidence: 99%